Fecundostilbum, a new genus of Stilbellaceae - PRAMEELA DEVI*, T. (Indian Phytopathology, 2009)
A new genus of Stilbellaceae, Fecundostilbum is described from the leaves of Saccharum officinarum. The new genus is characterized by the presence of single to synnematous conidiophores, setae, rhizoids, often twisted synnemata, internally and externally proliferated, branched, indeterminate, phialidic conidiophores and synnemata producing two types of conidia i.e., endogenous, 0-1 septate, cylindrical, guttulate, rough, double walled, brown, larger conidia and single walled, hyaline, smaller conidia, which in turn aggregates into slimy head after discharge. The type is F. saccharum sp. nov.